Experiences of a merger: the perspective of mid-level administrators in merged Kansas community and technical colleges - Ohman, Jessica, author; Anderson, Sharon, advisor; Banning, James, committee member; Kuk, Linda, committee member; Hall, Bruce, committee member (Colorado State University. Libraries, 2011)
This study was conducted to better understand the phenomenology of mid-level administrators employed at Kansas community or technical colleges/schools who experienced the merger process. An interpretative phenomenological analysis was used to examine individual life experiences. Eight mid-level administrators were interviewed for this study. The findings from this research confirm merger literature stressing the importance of leadership, communication, culture, collaboration and integration and how these factors impact the mid-level administrators' throughout the merger.
Keywords: experiences; merger; higher education